Electrically insulating resin composition and electrically insulating body

CN113614853BActive Publication Date: 2026-10-30RESONAC CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN201980094537.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2019-05-31
Publication Date
2026-10-30
Estimated Expiration
2039-05-31

AI Technical Summary

Technical Problem

[0009]但是,对于近年的浪涌电压值的上升,通过现有的电绝缘材料难以获得可充分令人满意的耐电压寿命特性

Benefits of technology

[0025]根据本发明,可以提供能够形成除了挠性、密合性及绝缘破坏电压特性等对于绝缘电线的绝缘皮膜所要求的代表性性能之外、还具有优异的部分放电劣化耐受性的绝缘皮膜,且具有优异的储存稳定性的电绝缘树脂组合物。另外,使用上述电绝缘树脂组合物可以提供绝缘可靠性高的电绝缘体。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113614853B_ABST
    Figure CN113614853B_ABST
Patent Text Reader

Abstract

The present invention relates to an electric insulating resin composition having a polyamide-imide resin, silica fine particles, and a dispersant having a phosphate group. Using the electric insulating resin composition, an electric insulator having excellent voltage endurance characteristics against surge voltage can be provided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure relates to an electrical insulating resin composition capable of forming an electrical insulator with excellent withstand voltage life characteristics against surge voltage, and an electrical insulator using the electrical insulating resin composition. Background Technology

[0002] In recent years, from the perspective of energy saving and variable speed control, electrical appliances using inverter control methods have been widely used in various fields. In particular, high efficiency is required in the control systems of hybrid vehicles and industrial engines. Therefore, as a variable speed device, the use of inverters for driving has seen rapid development in miniaturization, weight reduction, high heat resistance, and high-voltage drive.

[0003] In recent years, high-speed switching devices such as IGBTs (Insulated Gate Bipolar Transistors) have been developed as power devices for inverter drives. On the other hand, due to the high-speed switching of power devices and the increase in surge voltage, the frequency of early insulation failure and extremely shortened lifespan of motors and electrical appliances has increased.

[0004] One of the causes of the aforementioned insulation failure is the partial discharge that occurs when high voltage is applied to coils in motors via surges, leading to deterioration of the insulating film in electrical insulators. Therefore, for the purpose of extending the lifespan of motors and electrical appliances driven by inverters, it is desirable to develop electrical insulation materials that can suppress the deterioration of the insulating film caused by partial discharge.

[0005] On the other hand, due to its excellent processability, heat resistance, chemical resistance, and hydrolysis resistance, polyamide-imide resin is used as an important electrical insulating material in various applications. In particular, in the field of automotive engines (including hybrid vehicle engines), during the winding process in engine manufacturing, the winding wire is subjected to elongation, bending, and abrasion while under strong tension. Therefore, excellent processability, such as flexibility, is required for the winding wire.

[0006] Furthermore, winding cables are often installed in the presence of transmission fluid. Therefore, performance requirements for winding cables used in engines include resistance to corrosion by transmission fluid and tolerance to hydrolysis caused by moisture in the fluid. Moreover, the winding cables must also possess heat resistance to withstand high-temperature use. From this perspective, polyamide-imide resin becomes indispensable as an electrical insulation material used in winding cables (especially insulated wires).

[0007] Based on these perspectives, various studies have been conducted on electrical insulation materials that can suppress the deterioration of the insulating film caused by partial discharge (hereinafter also referred to as partial discharge degradation) and meet the representative performance requirements of insulated wires, such as processability, heat resistance, chemical resistance, and hydrolysis resistance.

[0008] For example, as an electrical insulating material capable of suppressing partial discharge degradation, a resin composition containing a polyamide-imide resin modified with a specific polybutadiene-based resin has been disclosed (Patent Document 1). Additionally, as other electrical insulating materials, resin compositions containing resins such as polyamide-imide resin and inorganic particles such as silica have been disclosed (Patent Documents 2-4).

[0009] However, given the recent increase in surge voltage values, existing electrical insulation materials are insufficient to achieve sufficiently satisfactory withstand voltage life characteristics. Therefore, there is a need for electrical insulation materials that offer higher tolerance to partial discharge degradation and improve withstand voltage life characteristics.

[0010] Existing technical documents

[0011] Patent documents

[0012] Patent Document 1: Japanese Patent Application Publication No. 2015-84329

[0013] Patent Document 2: Japanese Patent Application Publication No. 2001-307557

[0014] Patent Document 3: Japanese Patent Application Publication No. 2012-197367

[0015] Patent Document 4: Japanese Patent Application Publication No. 2008-251295 Summary of the Invention

[0016] The technical problem that the invention aims to solve

[0017] One method to improve the partial discharge degradation resistance of insulating films formed from electrical insulating materials containing resins such as polyamide-imide resin and inorganic particles such as silica, and to improve the withstand voltage life characteristics of electrical insulators, is to increase the content of inorganic particles. However, when the content of inorganic particles in the electrical insulating material is increased, there is a tendency for the flexibility of the insulating film, the adhesion to the conductor, and the insulation breakdown voltage to decrease. When the flexibility and adhesion of the insulating film are low, the insulation of insulated wires with such insulating films is easily reduced due to mechanical stress during winding processing. In addition, when the insulation breakdown voltage is low, insulation breakdown of the insulating film is more likely to occur not only during partial discharge. Furthermore, when the content of inorganic particles in the electrical insulating material is increased, there is a tendency for viscosity to increase and storage stability to decrease.

[0018] Therefore, for conventional electrical insulation materials containing inorganic particles, it is expected that while maintaining the representative characteristics required for the insulation film of insulated wires, such as flexibility, tightness, and insulation breakdown voltage, the partial discharge degradation tolerance, voltage withstand life characteristics, and storage stability can be improved.

[0019] Therefore, this disclosure provides an electrically insulating resin composition capable of forming an insulating film that, in addition to excellent flexibility, sealing properties, and insulation breakdown voltage characteristics, also exhibits excellent partial discharge degradation resistance and excellent storage stability. Furthermore, this disclosure provides an electrically insulating material using the aforementioned electrically insulating resin composition that has high insulation reliability.

[0020] Means for solving technical problems

[0021] The inventors have conducted in-depth research on electrically insulating resin compositions comprising polyamide-imide resin and inorganic particles. As a result, it was discovered that by using silica microparticles as inorganic particles and subsequently employing specific dispersants, it is possible to achieve an electrically insulating resin composition that maintains the representative characteristics required for the insulating film of insulated wires, such as flexibility, tightness, and insulation breakdown voltage characteristics, while simultaneously improving partial discharge degradation tolerance, enhancing withstand voltage life characteristics, and exhibiting excellent storage stability. Thus, the present invention is completed. That is, the present invention relates to the embodiments described below. However, the present invention is not limited to the following embodiments.

[0022] One embodiment relates to an electrically insulating resin composition comprising: a polyamide-imide resin; silica microparticles; and a dispersant having phosphate ester groups. Preferably, in the above electrically insulating resin composition, the amount of the dispersant having phosphate ester groups relative to 100 parts by weight of the silica microparticles is 5 to 20 parts by weight.

[0023] One embodiment relates to an electrical insulator comprising: a conductor; and an insulating film formed using the electrical insulating resin composition of the above embodiment. Preferably, the conductor is a metal wire.

[0024] Invention Effects

[0025] According to the present invention, an electrically insulating resin composition can be provided that, in addition to the representative properties required for the insulating film of insulated wires, such as flexibility, tightness, and insulation breakdown voltage characteristics, also has excellent partial discharge degradation resistance and excellent storage stability. Furthermore, using the above-described electrically insulating resin composition can provide an electrically insulator with high insulation reliability. Attached Figure Description

[0026] Figure 1 This is a schematic cross-sectional view illustrating one embodiment of an insulated wire.

[0027] Figure 2 This is a schematic cross-sectional view illustrating another embodiment of an insulated wire.

[0028] Figure 3 This is a schematic cross-sectional view illustrating another embodiment of an insulated wire.

[0029] Figure 4 This is a schematic cross-sectional view illustrating another embodiment of an insulated wire. Detailed Implementation

[0030] The embodiments of the present invention will be described in more detail below, but the present invention is not limited to the embodiments described below.

[0031] 1. Electrically insulating resin composition

[0032] One embodiment relates to an electrically insulating resin composition comprising: a polyamide-imide resin; silica microparticles; and a dispersant having phosphate ester groups. The components are described below.

[0033] [Polyamide-imide resin]

[0034] Polyamide-imide resin is a resin containing amide and imide bonds within its molecule. Polyamide-imide resin is obtained by reacting an acid component (hereinafter referred to as acid component (a)) containing a tricarboxylic anhydride or its derivative with a diisocyanate compound or a diamine compound (hereinafter referred to as component (b)). Electrically insulating resin compositions may contain one or more polyamide-imide resins.

[0035] (Acid component (a))

[0036] The tricarboxylic anhydride used as the acid component (a) above can be any tricarboxylic acid having an anhydride group that reacts with the isocyanate group or amino group in component (b). Tricarboxylic anhydrides or their derivatives can be used without particular restriction for the manufacture of polyamide-imide resins.

[0037] From the viewpoint of heat resistance, the tricarboxylic anhydride in acid component (a) preferably has a structure containing an aromatic group. In one embodiment, acid component (a) preferably contains a tricarboxylic anhydride represented by formula (I) or formula (II). Among these, trimellitic anhydride is particularly preferred from the viewpoint of heat resistance and cost. The tricarboxylic anhydrides represented by formula (I) or formula (II) may be used alone or in combination of two or more, depending on the purpose.

[0038] [Chemical Formula Number 1]

[0039]

[0040] In the formula, X1 It represents -CH2-, -CO-, -SO2-, or -O-.

[0041] [Chemical Formula Number 2]

[0042]

[0043] In another embodiment, acid component (a) may further comprise an acid component different from the aforementioned tricarboxylic anhydride. For example, as part of acid component (a), tetracarboxylic dianhydride may be further comprised as needed. Specific examples of tetracarboxylic dianhydride include pyromellitic dianhydride, 3,3',4,4'-benzophenone tetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 1,2,5,6-naphthalenetetracarboxylic dianhydride, 2,3,5,6-pyridinetetracarboxylic dianhydride, 1,4,5,8-naphthalenetetracarboxylic dianhydride, 3,4,9,10-perylenetetracarboxylic dianhydride, 4,4'-sulfonyl phthalic acid dianhydride, m-terphenyl-3,3',4,4'-tetracarboxylic dianhydride (3,3”,4,4”-m-terphenyltetracarboxylic dianhydride), 4,4'-oxydiphenyl dianhydride, 1,1,1,3,3,3- Hexafluoro-2,2-bis(2,3- or 3,4-dicarboxyphenyl)propane dianhydride, 2,2-bis(2,3- or 3,4-dicarboxyphenyl)propane dianhydride, 2,2-bis[4-(2,3- or 3,4-dicarboxyphenoxy)phenyl]propane dianhydride, 1,1,1,3,3,3-hexafluoro-2,2-bis[4-(2,3- or 3,4-dicarboxyphenoxy)phenyl]propane dianhydride, 1,3-bis(3,4-dicarboxyphenyl)-1,1,3,3-tetramethyldisiloxane dianhydride, butanetetracarboxylic acid dianhydride, bicyclo-[2,2,2]-oct-7-ene-2:3:5:6-tetracarboxylic acid dianhydride, etc.

[0044] (Component (b))

[0045] There are no particular limitations on diisocyanate or diamine compounds, as long as they are compounds having two isocyanate groups or amino groups within their molecules. In one embodiment, component (b) preferably comprises aromatic compounds having isocyanate groups or amino groups as shown in formulas (III), (IV) and (V).

[0046] [Chemical Formula Number 3]

[0047]

[0048] [Chemical Formula Number 4]

[0049]

[0050] [Chemical Formula Number 5]

[0051]

[0052] In the above formula, R 1 and R 2 Each of these elements independently represents a hydrogen atom, an alkyl group, an alkoxy group, or a hydroxyl group. Preferably, the alkyl or alkoxy group has 1 to 20 carbon atoms, more preferably 1 to 15 carbon atoms, and even more preferably 1 to 10 carbon atoms. At least one of the hydrogen atoms in the alkyl or alkoxy group may be substituted with a halogen atom such as a fluorine atom. In one embodiment, R... 1 and R 2 Ideally, each atom should be a hydrogen atom.

[0053] Y represents either an isocyanate group or an amino group.

[0054] X 2 This represents -CH2-, -C(=O)-, -S(=O)-, -SO2-, -O-, -S-, or -CR. 3 R 4 -

[0055] R 3 and R 4 Each of the above-mentioned alkyl or alkoxy groups independently represents an alkyl or alkoxy group. The alkyl or alkoxy groups are as previously described. In one embodiment, R... 3 and R 4 It is one or more substituents selected from alkyl, trifluoromethyl, trichloromethyl, and phenyl groups having 1 to 10 carbon atoms. In one embodiment, X 2 The preferred option is -CH2-.

[0056] Specific examples of aromatic diisocyanate compounds or aromatic diamine compounds represented by formulas (III), (IV), or (V) above include 4,4'-diisocyanate diphenylmethane, 4,4'-diisocyanate biphenyl, 3,3'-diisocyanate biphenyl, 3,4'-diisocyanate biphenyl, 4,4'-diisocyanate-3,3'-dimethylbiphenyl, 4,4'-diisocyanate-2,2'-dimethylbiphenyl, 4,4'-diisocyanate-3,3'-diethylbiphenyl, 4,4'-diisocyanate-2,2'-diethylbiphenyl, 4,4'-diisocyanate-3,3'-dimethoxybiphenyl, 4,4'- The compounds include diisocyanate-2,2'-dimethoxybiphenyl, 1,5-diisocyanate-naphthalene, 2,6-diisocyanate-naphthalene, 4,4'-diaminodiphenylmethane, 4,4'-diaminobiphenyl, 3,3'-diaminobiphenyl, 3,4'-diaminobiphenyl, 4,4'-diamino-3,3'-dimethylbiphenyl, 4,4'-diamino-2,2'-dimethylbiphenyl, 4,4'-diamino-3,3'-diethylbiphenyl, 4,4'-diamino-2,2'-diethylbiphenyl, 4,4'-diamino-3,3'-dimethoxybiphenyl, 4,4'-diamino-2,2'-dimethoxybiphenyl, 1,5-diaminonaphthalene, and 2,6-diaminonaphthalene. These compounds can be used alone or in combination of two or more.

[0057] Alternatively, aromatic diisocyanate compounds or aromatic diamine compounds such as toluene diisocyanate, phenylene diisocyanate, 4,4'-diisocyanate diphenyl ether, 2,2-bis[4-(4'-isocyanate phenoxy)phenyl]propane, toluene diamine, phenylene diamine, 4,4'-diamino diphenyl ether, and 2,2-bis[4-(4'-aminophenoxy)phenyl]propane can be used as diisocyanate compounds or aromatic diamine compounds.

[0058] Furthermore, as diisocyanate or diamine compounds, for example, hexamethylenediamine, 2,2,4-trimethylhexamethylenediamine, diaminoisophorone, bis(4-aminocyclohexyl)methane, 1,4-diaminotranscyclohexane, hydrogenated m-phenylene diisocyanate, hexamethylene diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, diisocyanate-based isophorone, bis(4-isocyanate-based cyclohexyl)methane, 1,4-diisocyanate-based transcyclohexane, hydrogenated m-phenylene diisocyanate, and other aliphatic or alicyclic diisocyanate compounds or diamine compounds can be used. However, when using the above-mentioned aliphatic or alicyclic compounds, it is preferable to also use the above-mentioned aromatic diisocyanate compounds or aromatic diamine compounds. From the viewpoint of the heat resistance of the obtained resin, the amount of the above-mentioned aliphatic or alicyclic compounds used is preferably 50 mol% or less of the total amount of diisocyanate or diamine compounds.

[0059] The aforementioned diisocyanate compounds or diamine compounds may also be used in combination with polyisocyanate compounds or polyamine compounds with more than three functions.

[0060] In one embodiment, 4,4'-diphenylmethane diisocyanate is particularly preferred as a diisocyanate compound or diamine compound, taking into account the balance of heat resistance, solubility, mechanical properties and cost.

[0061] In addition, to prevent changes over time, the product stabilized with an isocyanate group using an inhibitor can be used as needed. Examples of inhibitors include alcohols, phenols, and oximes, but there are no particular limitations.

[0062] (Ratio of acid component (a) to component (b))

[0063] The ratio (molar ratio of (b) / (a)) of component (b) (representing the diisocyanate compound or diamine compound) to acid component (a) in the manufacture of the above-mentioned polyamide-imide resin can be adjusted without particular restriction. If the above molar ratio is too small, it tends to be difficult to increase the molecular weight of the resin. On the other hand, when the above molar ratio is too large, the foaming reaction tends to become more intense, and the residue of unreacted components increases, and the stability of the resin tends to deteriorate.

[0064] In one embodiment, since the desired Mn and acid value are readily obtained, the molar ratio of component (b) to acid component (a) is preferably 0.6 to 1.4, more preferably 0.7 to 1.3, and particularly preferably 0.8 to 1.2. The above molar ratio is calculated as the ratio of the total moles of isocyanate groups and amino groups in the diisocyanate or diamine compound in component (b) to the total moles of carboxyl groups, anhydride groups, and any reactive hydroxyl groups contained in the acid component (a).

[0065] Polyamide-imide resins can be synthesized, for example, according to the following manufacturing methods.

[0066] (1) A method for synthesizing polyamide-imide resin by mixing acid component (a) and component (b) at one time and reacting them.

[0067] (2) A method for synthesizing an amide-imide oligomer with isocyanate groups at the end by reacting component (b) with acid component (a) in excess, and then adding acid component (a) to react and synthesize a polyamide-imide resin.

[0068] (3) A method for synthesizing an amide-imide oligomer having an acid or anhydride group at the end by reacting an excess of acid component (a) with component (b), and then adding acid component (a) and component (b) to react and synthesize a polyamide-imide resin.

[0069] (Reaction temperature, reaction time)

[0070] In any of the above methods, the reaction temperature is preferably in the range of 80–150°C. Furthermore, the reaction time is determined by considering the desired number-average molecular weight (Mn), and is typically preferably 1–10 hours.

[0071] (The solvent used in the reaction)

[0072] There are no particular limitations on the solvents (synthetic solvents) used in the synthesis of polyamide-imide resins. Examples of such solvents include polar solvents such as N-methyl-2-pyrrolidone, N,N-dimethylformamide, γ-butyrolactone, N,N'-dimethylpropenylurea [1,3-dimethyl-3,4,5,6-tetrahydropyrimidin-2(1H)-one], dimethyl sulfoxide, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, and sulfolane; aromatic hydrocarbon solvents such as xylene and toluene; and ketones such as methyl ethyl ketone and methyl isobutyl ketone.

[0073] The amount of synthetic solvent used is not particularly limited, but is preferably 50 to 180 parts by mass, more preferably 60 to 120 parts by mass, relative to 100 parts by mass of the combined acid component (a) and component (b). When the amount of synthetic solvent used is adjusted to the above range, the foaming reaction during synthesis can be suppressed, and the synthesis time can be adjusted appropriately.

[0074] (Molecular weight of polyamide-imide resin)

[0075] Generally, from the viewpoint of ensuring coating strength, the number average molecular weight (Mn) of the polyamide-imide resin used as an insulating material is preferably 5,000 or more, more preferably 10,000 or more, and even more preferably 12,000 or more. On the other hand, from the viewpoint of operability during coating, the Mn of the polyamide-imide resin is preferably 100,000 or less, more preferably 70,000 or less, and even more preferably 50,000 or less.

[0076] While not particularly limited, in one embodiment, a polyamide-imide resin with an Mn value of 12,000 to 30,000 is preferably used to form the polyamide-imide resin composition. More preferably, the Mn value of the polyamide-imide resin is 12,000 to 20,000. When a polyamide-imide resin with an Mn value within the above range is used, there is a tendency to further enhance the dispersibility improvement effect of the silica particles resulting from the use of the dispersant.

[0077] The manganese content (Mn) in polyamide-imide resins can be adjusted by factors such as the amount of raw materials added and the reaction time. For example, samples can be taken during resin synthesis and measured using gel permeation chromatography (GPC) with a standard curve of standard polystyrene. The reaction can be continued until the target Mn is obtained, thereby enabling management.

[0078] In another embodiment, the polyamide-imide resin preferably has an acid value of 30 to 50 mg KOH / g. More preferably, the acid value is 35 to 45 mg KOH / g. Here, the acid value refers to the number of milligrams (mg) of KOH required to neutralize 1 g of polyamide-imide resin, and is the total acid value of the carboxyl groups in the polyamide-imide resin and the carboxyl groups obtained after ring-opening the anhydride groups.

[0079] When using polyamide-imide resins with acid values ​​within the aforementioned range, there is a tendency for the polyamide-imide resin to dissolve or disperse more easily in the mixed solvents described later. Furthermore, the resulting polyamide-imide resin composition tends to become less prone to gelation over time. Moreover, while not limited by theory, it is believed that the dispersibility of the silica particles is improved through the interaction between the carboxyl groups in the resin and the silica particles described later.

[0080] (Silica particles)

[0081] Among representative inorganic particles used in electrical insulation materials, silica is preferred due to its excellent dispersibility in resins and the difficulty in particle aggregation. In particular, silica microparticles are preferred when combined with polyamide-imide resins.

[0082] In this specification, "silicon dioxide microparticles" refers to silicon dioxide (silicon oxide) with an average primary particle size of 50 nm or less. There are no particular limitations on the silicon dioxide microparticles except that the average primary particle size is 50 nm or less, and known silicon dioxide microparticles can be used.

[0083] In this specification, "average primary particle size" does not refer to the average particle size of aggregated particles (i.e., not secondary particle size), but rather to the average particle size of monomers that have not aggregated. The average primary particle size of silica microparticles can be typically determined using a laser diffraction particle size distribution measuring device or a transmission electron microscope (TEM). For example, in the TEM method, at least one hundred particles randomly selected from the composition or dispersion are first analyzed by measuring the area of ​​each particle image using TEM. Then, the diameter of a circle with the same area as the obtained area is taken as the particle size, and the average value of each particle size is calculated using known statistical processing, thereby obtaining the average primary particle size.

[0084] In one embodiment, from the viewpoint of film-forming properties and adhesion, the average primary particle size of the silica particles is preferably 40 nm or less, more preferably 30 nm or less, and even more preferably 20 nm or less. On the other hand, from the viewpoint of processability, the average primary particle size of the silica particles is preferably 3 nm or more, more preferably 5 nm or more, and even more preferably 10 nm or more. In one embodiment, the average primary particle size of the silica particles can be in the range of 10 to 20 nm, more preferably in the range of 10 to 15 nm.

[0085] Due to their small particle size, silica microparticles are expected to exhibit beneficial properties such as improved film-forming properties and adhesion of insulating films. On the other hand, compared to silica particles with an average primary particle size exceeding 50 nm, silica microparticles tend to be more prone to secondary aggregation and have reduced dispersibility. However, in the electrically insulating resin composition of the above embodiments, excellent dispersion stability can be easily obtained by using the dispersant with phosphate ester groups described later.

[0086] From the perspective of improving dispersibility in resins, silica microparticles can also be microparticles that have been treated with representative surface treatment agents such as silane coupling agents. As a specific example of a silane coupling agent, alkoxy-type silane coupling agents can be cited.

[0087] Furthermore, the silica particles can be used in the form of silica sol or as a solvent-displaced product. Here, silica sol refers to a dispersion in which silica particles are dispersed in a dispersion medium, and it has fluidity. The dispersion medium in the silica sol preferably has excellent compatibility with the aforementioned polyamide-imide resin. Examples of dispersion media include N,N-dimethylacetamide, methyl ethyl isobutyl ketone, water, or methanol. Alternatively, a mixture of xylene and butanol can also be used. In one embodiment, the dispersion medium may be the same as the mixed solvent described later.

[0088] While not particularly limited, in one embodiment, silica sol is preferably used as the silica particles. For example, silica sol containing N,N-dimethylacetamide as the dispersion medium can be preferably used. Generally, silica particles with an average primary particle size of 50 nm or less tend to undergo secondary agglomeration, but when using silica sol, there is a tendency to maintain good dispersibility and suppress particle sedimentation caused by agglomeration. In addition, the combination of silica sol and the dispersant with phosphate ester groups described later tends to obtain even better dispersion stability.

[0089] Silica sol can also be commercially available, but those skilled in the art can prepare it using known methods. For example, the conventional method of dispersing powder in a liquid can be used in the manufacture of silica sol. Examples include mixing silica particles, a dispersion medium, and other components such as a dispersant, and then dispersing the mixture using ultrasonic methods, mixer methods, three-roll mill methods, and ball mill methods. While not particularly limited, the amount of silica particles in the silica sol, based on the total mass of the silica sol, can range from 10% to 50% by mass, more preferably from 20% to 40% by mass.

[0090] In the electrically insulating resin composition of the above embodiments, the amount of silica microparticles relative to 100 parts by weight of the polyamide-imide resin is preferably 5 to 50 parts by weight. More preferably, the amount of silica microparticles is 10 to 40 parts by weight, and even more preferably 10 to 20 parts by weight. Adjusting the amount of silica microparticles to the above range makes it easier to improve partial discharge degradation tolerance while maintaining the representative characteristics required for insulated wires. When using a sol of silica microparticles, the above amount refers to the value calculated from the solid content of silica microparticles contained in the sol. By adjusting the amount of silica microparticles to the above range, partial discharge degradation tolerance can be improved without reducing the properties of the insulating film such as flexibility and adhesion, and withstand voltage life tolerance can be easily improved.

[0091] In one embodiment of the electrically insulating resin composition, the aforementioned silica particles can be combined with other inorganic particles within a range that maintains excellent dispersibility. For example, the aforementioned silica particles can be combined with silica with an average primary particle size exceeding 50 nm. Other inorganic particles that can be combined with silica include metal oxides such as alumina, titanium dioxide, magnesium oxide, or zirconium oxide. Other specific examples include clay, talc, barium sulfate, and calcium carbonate.

[0092] (Dispersants with phosphate ester groups)

[0093] Phosphate ester dispersants refer to compounds obtained by the condensation reaction of phosphoric acid or polyphosphoric acid with polymer compounds having hydroxyl groups, and compounds known as phosphate ester dispersants can be used.

[0094] Generally, dispersants with acidic groups exhibit adsorption properties to the surface of inorganic particles, and can improve dispersibility by inhibiting aggregation between inorganic particles. In the electrically insulating resin composition of this embodiment, the dispersibility of silica particles can be effectively improved by using a dispersant with phosphate ester groups for silica particles. As can also be seen from the examples described later, when using a dispersant with carboxylic acid groups rather than phosphate groups as acidic groups, there is a tendency to be difficult to obtain excellent dispersibility and voltage life characteristics.

[0095] A phosphate ester dispersant (hereinafter referred to as a phosphate ester dispersant) consists of a structural site (A) derived from a phosphate group in phosphoric acid or polyphosphoric acid and a polymer chain (B) in which at least a portion of the phosphate group is ester-bonded. The phosphate ester dispersant may be a structure in which one hydrogen atom of a hydroxyl group present in phosphoric acid or polyphosphoric acid is replaced by a polymer chain, or it may be a structure in which two hydrogen atoms of two hydroxyl groups present in phosphoric acid or polyphosphoric acid are each replaced by a polymer chain.

[0096] While not limited by theory, it is believed that in the electrically insulating resin composition of this embodiment, the structural portion (A) of the dispersant exhibits excellent adsorption to the surface of silica particles, and the polymer chain (B) repels the silica particles to each other due to steric hindrance with the polyamide-imide resin, thereby stabilizing the dispersion of the silica particles. That is, it can be considered that a portion of the phosphate dispersant improves dispersibility by adsorbing onto the surface of the silica particles, but it is speculated that even if the phosphate dispersant floats in the system, the steric hindrance can still improve the dispersibility of the silica particles.

[0097] While not particularly limited, the polymer chain (B) in the phosphate ester dispersant has a structure derived from a polymer compound with terminal hydroxyl groups, represented by the formula "B-OH". In one embodiment, the polymer chain (B) preferably has the structure "CH3-(X1)".a -(OX2) b The structure of polymer compounds derived from the general formula "-OH" is shown.

[0098] In the formula, X1 is a divalent organic group, preferably an alkylene group with 1 to 30 carbon atoms or an arylene group with 6 to 30 carbon atoms, or a combination thereof (alkylene arylene, etc.), and a is an integer of 0 or 1.

[0099] X2 is an alkylene group having 2 to 6 carbon atoms, and b is an integer from 5 to 15. The aforementioned alkylene group can be any of a straight-chain structure, a branched structure, or a cyclic structure, but a straight-chain structure is preferred.

[0100] The preferred site of the olefin oxide (OX2) is ethylene oxide, propylene oxide, or butane oxide.

[0101] Although not particularly limited, in one embodiment, the phosphate ester dispersant may be one or two hydroxyl hydrogen atoms present in phosphoric acid or polyphosphoric acid that are surrounded by "R-(CH2CH2O". b The structure indicated by the "-" signifies a substituted group. In the formula, R represents an alkyl group with 4 to 36 carbon atoms, or a phenyl group that can be substituted by an alkyl group, and b is an integer from 5 to 15.

[0102] The molecular weight of the polymer chain (B) portion in the phosphate ester dispersant is preferably 500 to 3,000, more preferably 700 to 2,000, and even more preferably 1,000 to 1,500. When the molecular weight of the polymer chain is within the above range, excellent dispersion effect can be easily obtained, and viscosity increase caused by interaction with resin components can be easily suppressed.

[0103] In one embodiment, the acid value of the phosphate ester dispersant is preferably 50 mg KOH / g or more, more preferably 70 mg KOH / g or more, further preferably 90 mg KOH / g or more, and most preferably 100 mg KOH / g or more. On the other hand, the acid value is preferably 240 mg KOH / g or less, more preferably 190 mg KOH / g or less, further preferably 150 mg KOH / g or less, and most preferably 140 mg KOH / g or less. In one embodiment, the acid value of the phosphate ester dispersant is preferably in the range of 70–150 mg KOH / g, more preferably in the range of 90–140 mg KOH / g, and even more preferably in the range of 100–135 mg KOH / g. Here, acid value refers to the number of milligrams (mg) of KOH required to neutralize 1 g of the phosphate ester dispersant.

[0104] Phosphate ester dispersants can be manufactured using phosphoric acid or polyphosphoric acid and polymer compounds containing hydroxyl groups according to known methods, but they are also available as commercially available products. For example, BYK Japan Co., Ltd.'s product names "DISPERBYK-102" and "DISPERBYK-W-9010" are preferred. These substances are compounds with an acid value of 100 to 135 mg KOH / g and a molecular weight of 1,000 to 1,500 in the polymer chain sites bonded to phosphate groups. Among them, when using "DISPERBYK-W-9010", in addition to improving dispersibility, it can also effectively suppress viscosity increase, thus easily obtaining excellent storage stability.

[0105] The amount of phosphate ester-based dispersant in the electrical insulating resin composition is not particularly limited. From the viewpoint of effectively improving the dispersibility of silica particles, it is preferably 5 parts by mass or more, more preferably 7 parts by mass or more, and even more preferably 10 parts by mass or more, relative to 100 parts by mass of silica particles (converted from solid content). On the other hand, the upper limit of the amount of phosphate ester-based dispersant is not particularly limited. From the viewpoint of suppressing the decline in film properties caused by polyamide-imide resin and silica particles, it is preferably 20 parts by mass or less. In one embodiment, the amount of phosphate ester-based dispersant relative to 100 parts by mass of silica particles is preferably 5 to 20 parts by mass, more preferably 7 to 18 parts by mass, and even more preferably 10 to 15 parts by mass.

[0106] The storage stability of the electrical insulating resin composition can be evaluated by the viscosity change over time (%) of the polyamide-imide resin composition (varnish) before and after storage. In one embodiment, when a certain amount of the polyamide-imide resin composition with a solid content of 10-50% by mass is placed in a sealed container and the sealed container is stored in a desiccator set at 25°C for 1 month, the viscosity change over time before and after storage is preferably the same as or less than the viscosity change over time of a varnish without silica particles.

[0107] In one embodiment, the viscosity change rate of the varnish over time is preferably 20% or less, more preferably 15% or less. However, if the initial viscosity of the electrical insulating resin composition is too high, even if the viscosity change rate over time is small, the processability tends to deteriorate if the initial viscosity is high. Therefore, the initial viscosity (Pa·s) of the electrical insulating resin composition is preferably 3.0 or less, more preferably 2.7 or less, and even more preferably 2.5 or less. Therefore, the varnish is more preferably in the above-mentioned range in terms of initial viscosity and viscosity change rate over time of 20% or less. When a phosphate ester dispersant is used for silica particles, an electrical insulating resin composition (varnish) with excellent processability and excellent storage stability can be easily formed.

[0108] (Mixed solvents)

[0109] In one embodiment, the electrically insulating resin composition may comprise the aforementioned polyamide-imide resin, the aforementioned silica microparticles, the aforementioned phosphate ester dispersant, and a solvent for mixing these components (hereinafter referred to as the mixed solvent). The mixed solvent is preferably a solvent capable of dissolving the polyamide-imide resin and may be the same as the synthetic solvent used in the synthesis of the aforementioned polyamide-imide resin. Therefore, to manufacture the electrically insulating resin composition, the reaction solution obtained during the manufacture of the polyamide-imide resin may also be used directly. In one embodiment, the synthetic solvent and the mixed solvent preferably comprise N-methyl-2-pyrrolidone and / or N,N-dimethylacetamide.

[0110] In the electrically insulating resin composition, the amount of synthetic solvent and / or mixed solvent is not particularly limited. The polyamide-imide resin can be diluted using synthetic solvent and / or mixed solvent, and the amount adjusted to obtain a viscosity suitable for the desired application. In one embodiment, the electrically insulating resin composition can be in the form of an electrically insulating coating (varnish) comprising polyamide-imide resin, silica microparticles, phosphate ester dispersant, and solvent. When the electrically insulating resin composition is used as a varnish, generally, the solid content is preferably 10-50% by mass, more preferably 20-40% by mass, based on the total mass of the varnish. By adjusting the solid content in the varnish to the above range, excellent coatability can be obtained, and thick films can be easily formed by repeated coating. The above-mentioned solid content can be representatively the total amount of polyamide-imide resin and silica microparticles.

[0111] (Other ingredients)

[0112] The electrically insulating resin composition may further include additives such as colorants, as needed. The amount of additives is preferably adjusted within a range that does not reduce the properties of the film.

[0113] The electrically insulating resin composition can be prepared by mixing and dispersing the above-mentioned polyamide-imide resin, the above-mentioned silica microparticles, the above-mentioned phosphate ester dispersant, and other components such as a mixed solvent and additives as needed, according to a known method. The mixing and dispersion process can be carried out using known mixing and dispersing machines such as high-speed mixers, homogenizers, ball mills, roller mills, and ultrasonic dispersers. When two or more mixing and dispersing machines are used in combination, a good dispersion state can be easily obtained.

[0114] In the preparation of the electrically insulating resin composition, the phosphate ester dispersant is used in an embodiment where it is mixed together with the polyamide-imide resin and silica microparticles. In another embodiment, the phosphate ester dispersant can also be used in a pre-mixing manner with the silica microparticles before preparing the electrically insulating resin composition. The phosphate ester dispersant can not only adhere to the surface of the silica microparticles, but also float in the system of the electrically insulating resin composition.

[0115] 2. Electrical insulators

[0116] The electrically insulating resin composition of the above embodiments can be preferably used as an electrically insulating material for imparting insulation to various conductors. One embodiment relates to an electrically insulating body having: a conductor; and an insulating film formed from the electrically insulating resin composition of the above embodiments for imparting insulation to the conductor. The insulating film can be formed by coating the electrically insulating resin composition of the above embodiments onto the conductor and then soldering it.

[0117] Examples of conductors mentioned above include metal wires such as copper wires, and structures for which other insulating properties are desired. In electrical insulators, in addition to the insulating film made of the aforementioned electrically insulating resin composition, the conductor may further have an additional insulating film made of other electrically insulating materials.

[0118] (conductor)

[0119] Examples of the aforementioned conductors include, for instance, metal wires described later or electrical and electronic components used in inverter control appliances. Electrical and electronic components endowed with an insulating film formed from the electrically insulating resin composition of the above embodiments are particularly useful for high-voltage applications and inverter control.

[0120] In electrical and electronic components subjected to high voltages, and in electrical and electronic components used in inverter control appliances, with the increase in surge voltage values ​​in recent years, there is a tendency for partial discharge degradation of the insulating film to occur and for the withstand voltage life to be short. However, the insulating film formed by the electrical insulating resin composition of the above embodiment has excellent partial discharge degradation resistance, and therefore can be preferably used in surge countermeasures for electrical and electronic components.

[0121] When the electrical insulating resin composition of the above embodiments is coated onto a metal wire, an insulated wire (enameled wire) with excellent partial discharge degradation resistance, while meeting representative performance requirements such as flexibility, processability, heat resistance, and insulation breakdown voltage characteristics, and with high insulation reliability can be provided. Furthermore, by using the insulated wire of the above embodiments, electrical and electronic components with high resistance to insulation breakdown and excellent withstand voltage life can be provided. In addition, insulation breakdown due to partial discharge is not limited to the insulating film of insulated wires; it can also occur in insulating films such as phase-to-phase insulating paper in electric motors, insulating varnish covering motor coils, insulated wires in electrical appliances such as generators, transformers, and switching devices, and in insulating components of filling molds. Therefore, the electrical insulating resin composition of the above embodiments can also be used to construct these insulating parts.

[0122] (Method for manufacturing insulating film)

[0123] There are no particular limitations on the method for applying the electrically insulating resin composition of the above embodiments, and techniques known in the art can be used. For example, when applying the electrically insulating resin composition prepared as an electrically insulating coating (varnish) onto an electrical wire (metal wire), methods such as molding and felt coating can be used.

[0124] The electrically insulating resin composition described above can be applied to a conductor, and then the coating is dried and cured to form an insulating film. The drying and curing of the coating can be achieved by heat treatment at a temperature of 260–520°C for 2 seconds to several minutes. When the heat treatment temperature is low, solvent residue may remain after drying and curing, leading to a decrease in coating properties. Furthermore, if the curing temperature is not high enough (e.g., below 260°C), the coating may not dry and cure sufficiently. If the heating time is too short, solvent residue remains in the coating, and the coating properties are easily degraded. On the other hand, if the heating time is too long, time and energy are wasted, and production efficiency is easily reduced.

[0125] The drying and curing method (welding method) of the electrically insulating resin composition coated on the metal wire (electric wire) can be carried out according to conventional methods. A representative example is the method of coating the electrically insulating resin composition onto the wire and then passing it through a heating oven. From the viewpoint of improving the resistance to insulation damage of the insulating film formed by the cured film formed by the above-described drying and curing, it is preferable to repeatedly apply the electrically insulating resin composition several times to form the insulating film.

[0126] The insulating film can be a single-layer structure or a multi-layer structure. While not particularly limited, in one embodiment, the overall thickness of the insulating film is preferably 20–200 μm, more preferably 40–150 μm. If the coating is too thin, the insulation becomes insufficient; if it is too thick, the conductor ratio and electrodynamic capability decrease when forming the coil. Furthermore, an excessively thick coating is detrimental to miniaturization and thinning.

[0127] (Insulated wire (enameled wire))

[0128] Next, as an example of the aforementioned electrical insulators, an insulated wire will be described in more detail. Figure 1 This is a schematic cross-sectional view illustrating one embodiment of an insulated wire. Figures 2-4 This is a schematic cross-sectional view illustrating other embodiments of insulated wires. Figure 1 The insulated wire A shown has a conductor 1 and an insulating film 2 formed by coating the conductor 1 with the electrically insulating resin composition of the above embodiment and welding it.

[0129] As a specific example of conductor 1, a metal wire such as copper wire can be cited. In one embodiment, the cross-sectional shape of the metal wire can be as follows: Figure 1 The diagram shows a circle. In another embodiment, the cross-sectional shape of the metal wire can also be square, rectangular, or square-angled.

[0130] The insulating film 2 can also be a multilayer structure formed by combining it with other electrically insulating materials. In this case, the insulating film becomes a multilayer structure with two or more layers of different electrically insulating materials stacked together. In this multilayer structure, the insulating film formed from the electrically insulating resin composition of the above embodiment can be the innermost layer in contact with the conductor, the outermost layer in contact with the outside, or an intermediate layer. Other electrically insulating materials include, for example, polyesterimide resin, polyurethane resin, polyester resin, polyimide resin, and polyamideimide resin that is essentially free of inorganic particles.

[0131] In one embodiment, the insulated wire A can be as follows: Figure 2 The diagram shows a structure with a primer layer 3 between the conductor 1 and the insulating film 2. In another embodiment, the insulated wire A can be as follows: Figure 3 The diagram shows a structure having a conductor 1, an insulating film 2, and a capping coating 4. Furthermore, in another embodiment, the insulated wire A may have a structure having a conductor 1, a primer layer 3, an insulating film 2, and a capping coating 4.

[0132] The primer layer and the capping layer described above are not particularly limited. From the viewpoint of compatibility with the resin of the insulating film 2, it is preferable to use a polyamide-imide resin that is essentially free of inorganic particles. The primer layer and the capping layer may contain less than 5 parts by weight of inorganic particles per 100 parts by weight of the polyamide-imide resin, but it is preferable to use only polyamide-imide resin. The polyamide-imide resin used to form the primer layer may be the same as the specific polyamide-imide resin constituting the electrical insulating resin composition of the above embodiment, but it is not particularly limited, and other polyamide-imide resins with a larger Mn may also be used. For example, in one embodiment, the Mn of the polyamide-imide resin used to form the primer layer and the capping layer may be 23,000 to 29,000.

[0133] As described above, the insulated wire A, by covering the conductor 1 with an insulating film 2 formed from the electrically insulating resin composition of the above embodiment, is endowed with flexibility, good workability, tightness, heat resistance, and insulation breakdown voltage characteristics, resulting in high insulation reliability. Therefore, the insulated wire of the above embodiment can preferably be used in the coils of a stator or rotor. Such a stator or rotor is equipped in an inverter drive engine or other high-voltage drive engine. Examples of inverter drive engines include engines for hybrid electric vehicles, engines for electric vehicles, engines for hybrid diesel vehicles, engines for electric two-wheeled vehicles, engines for elevators, and engines used in construction machinery.

[0134] Coils constructed using the insulated wires described above can provide high insulation reliability and extend the lifespan of electrical appliances or engines in the aforementioned applications. This effect is particularly pronounced in inverter control where higher voltages are applied. Furthermore, the aforementioned electrical insulating resin composition imparts sufficient insulation breakdown voltage characteristics even with a thin insulating film, thus contributing to the miniaturization and weight reduction of electrical appliances and engines.

[0135] Example

[0136] The present invention will now be described in detail through examples. However, the present invention is not limited to the examples described below, and various modifications can be made without departing from the spirit of the present invention.

[0137] <1> Preparation of polyamide-imide resin

[0138] In a flask equipped with a thermometer, stirrer, and cooling tube, 192.1 g (1.00 mol) of trimellitic anhydride, 250.3 g (1.00 mol) of 4,4'-diphenylmethane diisocyanate, and 362.0 g of N-methyl-2-pyrrolidone were placed. Then, under a stream of dry nitrogen, while monitoring the rapid bubbling of carbon dioxide gas produced by the reaction, the mixture was slowly heated to 130°C over approximately 6 hours, and then held at 130°C for 4 hours to obtain a polyamide-imide resin solution. This polyamide-imide resin solution was diluted with N,N-dimethylacetamide (DMAC) and then held at 200°C for 2 hours to prepare a polyamide-imide resin solution with a resin concentration (solid content) of 40%. Analysis of the polyamide-imide resin in the resulting solution showed a number-average molecular weight of 21,000 and an acid value of 40 mg KOH / g.

[0139] The number-average molecular weight and acid value of polyamide-imide resin were determined as follows.

[0140] (Number average molecular weight (Mn))

[0141] The conditions for the measurement are as follows.

[0142] GPC Model: Hitachi L6000

[0143] Detector: Hitachi L4000 UV

[0144] Wavelength: 270nm

[0145] Data processor: AT&T 8

[0146] Column: Gelpack GL-S300MDT-5 (×2)

[0147] Column dimensions: 8mmφ×300mm

[0148] Solvent: DMF / THF = 1 / 1 (L) + 0.06M phosphoric acid + 0.06M lithium bromide

[0149] Sample concentration: 5 mg / 1 ml

[0150] Injection volume: 5μl

[0151] Pressure: 49 kgf / cm 2 (4.8×10 6 Pa)

[0152] Flow rate: 1.0 ml / minute

[0153] (Acid value)

[0154] Collect 0.5 g of polyamide-imide resin, add 0.15 g of 1,4-diazabicyclo[2,2,2]octane, then add 60 g of N-methyl-2-pyrrolidone and 1 mL of deionized water, and stir until the polyamide-imide resin is completely dissolved. Titrate the solution thus obtained using a 0.05 mol / L alcoholic potassium hydroxide solution using a potentiometric titration apparatus.

[0155] <2> Preparation of Electrically Insulating Resin Composition

[0156] (Example 1)

[0157] A resin composition for electrical insulation was obtained by mixing and dispersing 100 parts by weight of a previously prepared polyamide-imide resin solution (with DMAC added to adjust the solid content to 37%), 12.3 parts by weight of silica sol, and 0.37 parts by weight of a phosphate ester dispersant at 60–70°C for 1 hour. The silica sol contained 30% by weight of silica with an average primary particle size of 11 nm, and the DMAC content as the dispersion medium was 70% by weight. The phosphate ester dispersant used was BYK Japan Co., Ltd.'s product name "DISPERBYK-W-9010" (acid value 129 mg / KOH).

[0158] In the obtained insulating resin composition, the amount of silica microparticles relative to 10 parts by mass of polyamide-imide (PAI) resin is 10 parts by mass. Additionally, the amount of phosphate dispersant (denoted as dispersant A in Table 1) relative to 100 parts by mass of silica microparticles is 10 parts by mass.

[0159] (Example 2)

[0160] In the preparation of the electrically insulating resin composition of Example 1, the electrically insulating resin composition was prepared in the same manner as in Example 1, except for changing the amount of silica sol used. Specifically, 100 parts by weight of the previously prepared polyamide-imide resin solution (with DMAC added to adjust the solid content to 37%), 18.5 parts by weight of silica sol, and 0.56 parts by weight of phosphate dispersant were mixed and dispersed at 60-70°C for 1 hour to obtain the electrically insulating resin composition.

[0161] In the resulting electrically insulating resin composition, the amount of silica particles relative to 100 parts by weight of polyamide-imide resin is 15 parts by weight. Additionally, the amount of phosphate dispersant relative to 100 parts by weight of silica particles is 10 parts by weight.

[0162] (Example 3)

[0163] In the preparation of the electrically insulating resin composition in Example 2, the electrically insulating resin composition was prepared in the same manner as in Example 2, except for changing the amount of phosphate dispersant used. Specifically, 100 parts by weight of the previously prepared polyamide-imide resin solution (with DMAC added to adjust the solid content to 37%), 18.5 parts by weight of silica sol, and 1.1 parts by weight of phosphate dispersant were mixed and dispersed at 60–70°C for 1 hour to obtain the electrically insulating resin composition.

[0164] In the resulting electrically insulating resin composition, the amount of silica particles relative to 100 parts by weight of polyamide-imide resin is 15 parts by weight. Additionally, the amount of phosphate dispersant relative to 100 parts by weight of silica particles is 20 parts by weight.

[0165] (Comparative Example 1)

[0166] In the preparation of the electrical insulating resin composition in Example 2, the electrical insulating resin composition was prepared in the same manner as in Example 2, except that the phosphate ester dispersant was replaced with a carboxyl-containing dispersant (product name "Flowlen G-700" manufactured by Kyoei Chemical Co., Ltd., with an acid value of 60 mg / KOH). Specifically, 100 parts by weight of the previously prepared polyamide-imide resin solution (with DMAC added to adjust the solid content to 37%), 18.5 parts by weight of silica sol, and 0.56 parts by weight of the carboxyl-containing dispersant were mixed and dispersed at 60–70°C for 1 hour to obtain the electrical insulating resin composition.

[0167] In the resulting electrically insulating resin composition, the amount of silica particles relative to 100 parts by mass of polyamide-imide resin is 15 parts by mass. Additionally, the amount of a carboxyl-containing dispersant (denoted as dispersant B in Table 1) relative to 100 parts by mass of silica particles is 10 parts by mass.

[0168] (Comparative Example 2)

[0169] In the preparation of the electrically insulating resin composition of Example 1, the electrically insulating resin composition was prepared in the same manner as in Example 1, except that a phosphate ester dispersant was not used. Specifically, 100 parts by weight of the previously prepared polyamide-imide resin solution (with DMAC added to adjust the solid content to 37%) and 12.3 parts by weight of silica sol were mixed and dispersed at 60–70°C for 1 hour to obtain the electrically insulating resin composition.

[0170] In the obtained electrically insulating resin composition, the amount of silica particles relative to 10 parts by mass of polyamide-imide resin is 10 parts by mass.

[0171] (Comparative Example 3)

[0172] In the preparation of the electrically insulating resin composition of Example 2, the electrically insulating resin composition was prepared in the same manner as in Example 2, except that a phosphate ester dispersant was not used. Specifically, 100 parts by weight of the previously prepared polyamide-imide resin solution (with DMAC added to adjust the solid content to 37%) and 18.5 parts by weight of silica sol were mixed and dispersed at 60–70°C for 1 hour to obtain the electrically insulating resin composition.

[0173] In the obtained electrically insulating resin composition, the amount of silica particles relative to 100 parts by weight of polyamide-imide resin is 15 parts by weight.

[0174] (Comparative Example 4)

[0175] DMAC was further added to the previously prepared polyamide-imide resin solution (with DMAC added and the solid content adjusted to 37%) to prepare an electrically insulating resin composition (with a solid content of 34%) that does not contain silica sol and phosphate dispersant.

[0176] <3> Evaluation of electrically insulating resin compositions

[0177] <3-1> Characteristics of Varnish

[0178] (Storage stability)

[0179] For the electrically insulating resin compositions (varnishes) of Examples 1-3 and Comparative Examples 1-4, the viscosity change over time (%) before and after storage at 25°C for 1 month was calculated according to the following order.

[0180] First, the viscosity of the polyamide-imide resin composition (varnish) was measured before storage. Next, a certain amount of the resin composition (varnish) was placed in a sealed container and stored in a desiccator set at 25°C for one month, after which the viscosity was measured. The viscosity change over time was calculated from each measured value according to the following formula (1).

[0181] (Equation 1)

[0182] Viscosity change rate over time (%) = (V2 - V1) / V1 × 100

[0183] In Formula 1, “V1” represents the initial viscosity measured before storage. “V2” represents the viscosity measured after storage at 25°C for one month.

[0184] Furthermore, all viscosity measurements were performed according to JIS C 2103 using a type B rotational viscometer at 25°C, rotor number 3, and rotation speed of 30 rpm. The values ​​obtained from the viscosity measurements are shown in Table 1.

[0185] <3-2> Characteristics of Insulated Wires (Characteristics of Insulating Film)

[0186] The electrical insulating resin compositions obtained in Examples 1-3 and Comparative Examples 1-4 were coated onto copper wires with a diameter of 1.0 mm and then soldered to manufacture an insulated wire having an insulating film with a thickness of 0.034 mm.

[0187] The manufacturing conditions and the method for measuring the thickness of the insulating film are described below.

[0188] (Conditions for coating and welding)

[0189] Welding furnace: Hot blast vertical furnace (furnace length 5m)

[0190] Number of coating passes: 8 times of die extrusion (repeatedly coating and welding 8 times).

[0191] Oven temperature: Inlet (evaporation zone) / Outlet (curing zone) = 320℃ / 430℃

[0192] Line speed: 16m / minute

[0193] (Determination of insulating film thickness)

[0194] The insulation thickness of the wire is obtained as follows: Use a micrometer to measure the diameter of the insulated wire (D1), then measure the diameter of the wire after the insulation has been burned off (D2), and divide the difference by 1 / 2 to obtain the thickness.

[0195] The properties of the insulating film of the obtained insulated wire were tested and evaluated using the following methods. The results are shown in Table 1.

[0196] (1) Withstand voltage lifetime characteristics (partial discharge degradation tolerance)

[0197] Using the previously prepared insulated wire, prepare two twisted test specimens as specified in JIS C3216-5. Then, apply a rectangular wave AC voltage of 20 kHz to the specimen at a test temperature of 155 ± 3 °C and a pulse voltage of 3000 V, and measure the time until the insulation of the specimen fails.

[0198] A voltage withstand life of 5 hours or more is a practical range, but a voltage withstand life of 20 hours or more is preferred, and more preferably 40 hours or more is preferred.

[0199] (2) Flexibility

[0200] The measurements were performed according to JIS C3216-3. The previously prepared insulated wire was wound with 20% elongation, and the diameter of any undetectable cracks in the insulation film was visually observed, as shown in Table 1. If no cracks were observed at twice the diameter, it was within the practical range; however, cracks exceeding three times the diameter were not preferred from a practical standpoint.

[0201] (3) Fit

[0202] According to JIS C3216-3, the insulating film that has been welded and left for more than one day is twisted at a speed of 100 times / min, and the speed at which the film peels off is measured. If the speed is above 80 times, it is within the practical range; if the speed is less than 80 times, it is not preferred from a practical point of view.

[0203] (4) Resistance to softening (heat resistance)

[0204] Using previously manufactured insulated wires, measurements were taken according to JIS C3216-6. A softening temperature of 400°C or higher is practically acceptable, while temperatures below 400°C are not preferred from a practical standpoint. A softening temperature of 450°C or higher is preferred, and 480°C or higher is more preferable.

[0205] (5) Insulation breakdown voltage characteristics

[0206] Using previously manufactured insulated wires, measurements were taken according to JIS C3216-5. If the insulation breakdown voltage is 9kV or higher, it is within the applicable range. Preferably, the insulation breakdown voltage is 10kV or higher, more preferably 11kV or higher.

[0207] The evaluation results are shown in Table 1. In Table 1, dispersant A represents a phosphate ester dispersant, and dispersant B represents a carboxyl-containing dispersant. The amount of dispersant is expressed as the amount of dispersant relative to 100 parts by mass of silica particles. The amount of silica particles is expressed as the amount of silica particles relative to 100 parts by mass of polyamide-imide resin. In addition, the solid content of the varnish is expressed as a value calculated from the total mass of polyamide-imide resin, silica particles, and dispersant relative to the total mass of the varnish.

[0208]

[0209] As shown in Table 1, compared to Comparative Examples 1-4, the electrical insulating resin compositions obtained in Examples 1-3 exhibited lower viscosity change over time and better storage stability through the use of a phosphate ester dispersant. Furthermore, it is evident that the insulated wires having an insulating film formed from the electrical insulating resin compositions obtained in Examples 1-3 showed significantly improved withstand voltage life compared to the insulated wires obtained in Comparative Examples 1-4, and other representative properties of the insulating film were also superior. In particular, a comparison with Comparative Example 1, which used a dispersant with carboxyl groups, reveals that in Examples 1-3, corresponding to embodiments of the present invention, the combination of a specific dispersant—a phosphate ester dispersant—with silica particles allows for improved withstand voltage life even with the addition of silica, without reducing representative properties of the insulating film such as adhesion, flexibility, and insulation breakdown voltage.

[0210] Thus, according to the present invention, a preferred electrically insulating resin composition can be provided as an electrically insulating material for forming an insulating film. Using this electrically insulating resin composition, an electrically insulating body with excellent voltage withstand life can also be provided. In particular, the electrically insulating resin composition of the present invention is useful for improving the long-term reliability of inverter drive motors that are increasingly operating at higher frequencies and voltages.

Claims

1. An electrically insulating resin composition for forming an electrically insulating body comprising an insulated wire, comprising: Polyamide-imide resin; Silica microparticles with an average primary particle size of 10-50 nm; and Dispersants with phosphate ester groups, The amount of silica microparticles relative to 100 parts by weight of the polyamide-imide resin is 5 to 20 parts by weight. The dispersant with phosphate ester groups consists of a structural site (A) derived from a phosphate group in phosphoric acid or polyphosphoric acid and a polymer chain (B) in which at least a portion of the phosphate group is ester-bonded. Its acid value is 100-135 mg KOH / g. The polymer chain (B) in the dispersant having phosphate ester groups has CH3-(X1) a -(OX2) b The polymer compound derived from the general formula -OH has a molecular weight of 1,000 to 1,500 at the (B) site of the polymer chain. In the general formula, X1 is a divalent organic group, a is an integer of 0 or 1, X2 is an alkylene group with 2 to 6 carbon atoms, and b is an integer of 5 to 15.

2. The electrically insulating resin composition according to claim 1, wherein, The amount of the dispersant with phosphate ester groups is 5 to 20 parts by mass relative to 100 parts by mass of the silica particles.

3. The electrically insulating resin composition according to claim 1 or 2, wherein, The acid value of the polyamide-imide resin is 30~50 mgKOH / g.

4. The electrically insulating resin composition according to claim 1 or 2, wherein, The polyamide-imide resin has a number average molecular weight of 5,000 or more and 100,000 or less.

5. The electrically insulating resin composition according to claim 1 or 2, further comprising a solvent.

6. An electrical insulator having: conductor; and An insulating film formed using the electrically insulating resin composition according to any one of claims 1 to 5.

7. The electrical insulator according to claim 6, wherein, The conductor is a metal wire.

8. A method for manufacturing an electrical insulator, comprising: a conductor and an insulating film formed using an electrically insulating resin composition; the method comprising: The electrically insulating resin composition according to any one of claims 1 to 5 is prepared by mixing and dispersing polyamide-imide resin, silica microparticles with an average primary particle size of 10-50 nm, and a dispersant with phosphate ester groups; and An insulating film is formed by coating the conductor with the electrically insulating resin composition and then soldering it.

9. The method for manufacturing an electrical insulator according to claim 8, wherein, In the preparation of the electrically insulating resin composition, silica sol is used as the silica particles.

Citation Information

Patent Citations

  • Coating material for partial discharge resistant enameled wire and partial discharge resistant enameled wire

    JP2001307557A

  • Insulated wire

    JP2008251295A

  • Insulating coating material, and insulating electric wire using the same

    JP2012197367A

  • Modified polyamide-imide resin, electrical insulation material, insulating layer dielectric breakdown resistance improvement method and insulated wire

    JP2015084329A

  • Corona discharge-resistant insulating varnish composition comprising surface-treated silica and insulated wire having insulated layer formed using the same

    CN102732146A